2020
DOI: 10.1002/hbm.25123
|View full text |Cite
|
Sign up to set email alerts
|

Eyes wide shut: How visual cues affect brain patterns of simulated gait

Abstract: In the last 20 years, motor imagery (MI) has been extensively used to train motor abilities in sport and in rehabilitation. However, MI procedures are not all alike as much as their potential beneficiaries. Here we assessed whether the addition of visual cues could make MI performance more comparable with explicit motor performance in gait tasks. With fMRI we also explored the neural correlates of these experimental manipulations. We did this in elderly subjects who are known to rely less on kinesthetic inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Indeed, the activation of visual hand representation in the lateral occipitotemporal cortex, integrating multisensory information, could feed the premotor and parietal cortex [8,[45][46][47][48] for planning the motor simulation steps of motor imagery [8,48,55]. However, it is important to bear in mind that a recent study on explicit motor imagery in elders has shown that the more the participants relied on visual information during motor imagery (with stronger occipitotemporal activation), the more inaccurate they were in judging the time needed to imagine walking a path [56]. Thus, targeting visual areas to facilitate motor imagery could represent a specific strategy in rehabilitation settings with patients who are able to exploit visual information to imagine movements.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the activation of visual hand representation in the lateral occipitotemporal cortex, integrating multisensory information, could feed the premotor and parietal cortex [8,[45][46][47][48] for planning the motor simulation steps of motor imagery [8,48,55]. However, it is important to bear in mind that a recent study on explicit motor imagery in elders has shown that the more the participants relied on visual information during motor imagery (with stronger occipitotemporal activation), the more inaccurate they were in judging the time needed to imagine walking a path [56]. Thus, targeting visual areas to facilitate motor imagery could represent a specific strategy in rehabilitation settings with patients who are able to exploit visual information to imagine movements.…”
Section: Discussionmentioning
confidence: 99%
“…The recruitment of visuospatial cortical areas by PD patients during MI is particularly remarkable given that most MI paradigms did not include external visual input or feedback to guide MI of gait. Note that, in a sample of healthy older participants, an increase in the activation of temporal and parietal regions was only observed when visual cues were provided during a MI task compared to MI without visual cues ( Zapparoli et al, 2020 ). Together these observations further corroborate the notion that PD patients, especially those with FoG, heavily rely upon visual strategies and visuomotor coordination to guide their gait.…”
Section: Task-based Imaging Studies Of Fog In Parkinson’s Diseasementioning
confidence: 99%
“…Cross et al (2006) observed a modulation of brain reactivity (within the inferior parietal lobule and ventral premotor cortex) as a function of the dancers' self-ratings of their own ability to perform the observed movements, as well as according to their training experience with the dance sequence. Other fMRI studies used comparable fMRI procedures, that is, by asking participants to project themselves into the realization of an action guided by external cues rather than simply imagining themselves performing a movement or to passively observing the movements of others (Conson et al, 2009;Di Nota et al, 2016;Nedelko et al, 2012;Vogt et al, 2013;Vrana et al, 2015;Villiger et al, 2013;Zapparoli et al, 2020). These studies show that action simulation under visual guidance elicits stronger cortical activations within the action simulation brain network than conventional "eyes-closed" imagined movement procedure.…”
Section: Introductionmentioning
confidence: 99%
“…These studies show that action simulation under visual guidance elicits stronger cortical activations within the action simulation brain network than conventional "eyes-closed" imagined movement procedure. For example, a recent study by Zapparoli et al (2020) showed that the addition of a visual cue to guide the mental simulation of walking (in-motion visual stimuli of a path in a park shown from a first-person perspective) increased temporo-occipito-parietal activation, as compared to the simulation of walking with eyes closed (to imagine walking along a path).…”
Section: Introductionmentioning
confidence: 99%